The Epistemology of Muhammad Syahrur’s Islamic Thought and Its Implications for the Study of Polygamy Hadith - Rohmansyah, Rohmansyah (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
Islamic epistemological discourse, such as polygamy, contains a variety of opinions (multi-opinion). Polygamy is a debate among Muslim scholars. Some argue that polygamy is permissible, while others prohibit it. On the other hand, the Qur’an and hadith allow polygamy as long as certain conditions are met. This article aims to explain the epistemology of Muhammad Syahrur's Islamic thought and its implications for the study of polygamy hadith. This is qualitative research based on library data reference sources. The research findings show that: First, the study of Muhammad Syahrur's Islamic epistemology is based on three important aspects, namely the condition of being (al-kainūnah), the condition of process (As-Sairūrah) and the condition of becoming (As-Hairūrah). Second, Muhammad Syahrur's thoughts are based on the logic of historical aspects of the past which refer to the polygamy hadith regarding the conditions for polygamy, namely 1) a polygamous woman is both a widow and a mother (having children); and 2) a man who practices polygamy must fairly provide physical and spiritual support to their wives and children. This thinking is based on Syahrur's scientific epistemology in constructing religious studies. Third, Muhammad Syahrur's scientific epistemology is influenced by four aspects, namely mihwar regarding philosophy, theological, anthropological, and naturalistic regarding environmental or natural conditions.